Dear Haiti, love Alaine - Moulite, Maika; Moulite, Maritza (Inkyard Press, 2019)
After an incident at school, seventeen year-old Alaine is spending spring break in a "volunteer immersion project", toiling away under the ever-watchful eyes of Tati Estelle and her eagle-eyed mother at a new nonprofit in Haiti. Although it is meant as punishment, Alaine is still able to flirt with Tati's distractingly cute intern, get some actual face time with her mom and experience her family's history in Haiti for the first time
Keywords: Teenagers / Fiction; Students / Fiction; Voluntarism / Fiction; Community service (Punishment) / Fiction; Mothers and daughters / Fiction; Families / History / Fiction; Haitian Americans / Fiction; Student suspension / Fiction; Report writing / Fiction; Coming of age / Fiction; YOUNG ADULT FICTION / Epistolary (Letters & Diaries); YOUNG ADULT FICTION / Diversity & Multicultural; YOUNG ADULT FICTION / People & Places / Caribbean & Latin America; Voluntarism; Teenagers; Students; Mothers and daughters; Families; Community service (Punishment); Haitian Americans / Juvenile fiction; Report writing / Juvenile fiction; Adolescence / Fiction; Bericht; Mutter; Sozialdienst; Haitianer; Tochter; Weibliche Jugend -- 17 Jahre; Haiti / Fiction; Haiti; Haiti / Juvenile fiction; USA; Jugendbuch